Thermo-mechanical fatigue life prediction based on the simulated component of cylinder head. (May 2022) - Yang, Wenjun; Pang, Jianchao; Wang, Lei; Kang, Xin; Zhou, Song; Zou, Chenglu; Li, Shouxin; Zhang, Zhefeng
Highlights: Simulated component of cylinder head is established based on the equivalent model of flame deck. The simulation method of thermo-mechanical fatigue is developed by the Sehitoglu theory and loading spectrums. Damage characteristics at typical working condition are predicted from three damage types. Abstract: As the vulnerable component of diesel engine, cylinder head is subjected to the thermo-mechanical coupling loads more and more heavily. For establishing a simple and effective technology to evaluate the damage degree, a prediction method based on simulated component is developed in the present work. By the comparison of temperature and stress at measured points, it shows that the simulation and testing results have a good agreement, verifying the effectiveness of simulated component. Applying Sehitoglu theory and loading spectrums, the failure locations are predicted successfully. Then damage characteristics of thermo-mechanical fatigue are analyzed at failure locations. It indicates that mechanical damage takes a leading role compared with oxidative damage and creep damage, and thermal load is more sensitive to mechanical damage in three damage types. This study may provide an effective way to estimate the service life of cylinder head.